2018
DOI: 10.1021/jacs.8b05341
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Strings Significantly Improved the Gene Transfection Efficiency of Polycations

Abstract: High transfection efficiency and low cytotoxicity are the two key factors to be considered in the design of gene carriers. Herein, a novel and versatile gene carrier (PLL-RT) was prepared by introducing "molecular string" RT (i.e., p-toluylsulfonyl arginine) onto the polylysine backbone. The introduction of RT string contributed to the formation of multiple interactions between the polycationic gene carriers and cell membrane or DNA, as well as adopting α-helix conformation, all of which would be beneficial to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 57 publications
0
88
0
Order By: Relevance
“…To explore whether the cationic and anionic combination of ILs influenced the internalization, the binding constant between ILs and cardiolipin (CL) was measured by isothermal titration calorimetry (ITC). CL contained long hydrophobic alkyl chains and phosphate groups, which shared a similar molecular structure with phospholipid, the main component in cell membrane ( 37 ); thereby, the binding constant between ILs and CL could reflect the discrepancy in cell internalization. The titration curves and thermodynamic analysis demonstrated that the binding constant of [Ch][APA] with CL was significantly higher than that of [Ch][Tau] or [EMIm][APA], which might facilitate the cell internalization of [Ch][APA] (fig.…”
Section: Resultsmentioning
confidence: 99%
“…To explore whether the cationic and anionic combination of ILs influenced the internalization, the binding constant between ILs and cardiolipin (CL) was measured by isothermal titration calorimetry (ITC). CL contained long hydrophobic alkyl chains and phosphate groups, which shared a similar molecular structure with phospholipid, the main component in cell membrane ( 37 ); thereby, the binding constant between ILs and CL could reflect the discrepancy in cell internalization. The titration curves and thermodynamic analysis demonstrated that the binding constant of [Ch][APA] with CL was significantly higher than that of [Ch][Tau] or [EMIm][APA], which might facilitate the cell internalization of [Ch][APA] (fig.…”
Section: Resultsmentioning
confidence: 99%
“…367 Recently, modifications of PLL 120 with p-toluylsulfonyl arginine resulted in change of conformation from random coil to α-helix, which gave higher DNA-transfection rates due to higher cell-permeability. 370 Layer-by-layer depositionreferred to as protein surface precipiation hereof PLL and dextran sulfate sodium salt were applied onto Ad surface to obtain nanospheres that protect Ad from antigenic reactions and thereby enhanced TE (Fig. 14A).…”
Section: Reviewmentioning
confidence: 99%
“…Dendrimers are flexible gene delivery vehicles to the injured site as they carry a positive charge and smaller in size. [169][170][171] Dendrimers have repeated branches with low polydispersity and high molecular uniformity. Drug moieties have loaded into the cavities and branch folding's, which forms into the shape of channels and cages.…”
Section: Dendrimersmentioning
confidence: 99%